Acute β‐Hydroxy‐β‐Methyl Butyrate Suppresses Regulators of Mitochondrial Biogenesis and Lipid Oxidation While Increasing Lipid Content in Myotubes. Issue 10 (6th September 2016) - Schnuck, Jamie K.; Johnson, Michele A.; Gould, Lacey M.; Gannon, Nicholas P.; Vaughan, Roger A.
Abstract: Leucine modulates synthetic and degradative pathways in muscle, possibly providing metabolic benefits for both athletes and diseased populations. Leucine has become popular among athletes for improving performance and body composition, however little is known about the metabolic effects of the commonly consumed leucine‐derived metabolite β‐hydroxy‐β‐methyl butyrate (HMB). Our work measured the effects of HMB on metabolic protein expression, mitochondrial content and metabolism, as well as lipid content in skeletal muscle cells. Specifically, cultured C2C12 myotubes were treated with either a control or HMB ranging from 6.25 to 25 μM for 24 h and mRNA and/or protein expression, oxygen consumption, glucose uptake, and lipid content were measured. Contrary to leucine's stimulatory effect on metabolism, HMB‐treated cells exhibited significantly reduced regulators of lipid oxidation including peroxisome proliferator‐activated receptor alpha (PPARα) and PPARβ/δ, as well as downstream target carnitine palmitoyl transferase, without alterations in glucose or palmitate oxidation. Furthermore, HMB significantly inhibited activation of the master regulator of energetics, AMP‐activated protein kinase. As a result, HMB‐treated cells also displayed reduced total mitochondrial content compared with true control or cells equivocally treated with leucine. Additionally, HMB treatment amplified markers of lipid biosynthesis (PPARγ and fatty acid synthase) as well as consistently promoted elevated total lipid content versus control cells. Collectively, our results demonstrate that HMB did not improve mitochondrial metabolism or content, and may promote elevated cellular lipid content possibly through heightened PPARγ expression. These observations suggest that HMB may be most beneficial for populations interested in stimulating anabolic cellular processes.